Association of maternal folic acid supplementation and incidence of non-syndromic cleft lip and palate - Hendry Rusdy; I. Isnandar; Indra Basar Siregar; Rizkiani Cahya Putri Sinaga (Universitas Airlangga, 2022)
Background: Cleft lip and palate as a frequent congenital defect is caused by genetic and environmental factors. Micronutrient folic acid as an environmental factor has shown a role as a cleft lip and palate protective factor in several previous studies. Purpose: The purpose of this study was to determine the distribution of adequacy of folic acid supplementation and the association between folic acid supplementation during the first trimester of pregnancy with the incidence of cleft lip and palate at Mitra Sejati Hospital, Medan, North Sumatra, Indonesia. Methods: This study used analytical research with a case-control design and questionnaire. A Chi-square test was used to observe the association between the folic acid supplement intake during the first trimester with the incidence of cleft. The p-value ≤ 0.05 was deemed to be significant. Results: The study found that 47 mothers (51.09%) had insufficient, while 45 mothers (48.91%) had adequate folic acid supplementation. This study did not show a significant association between supplement use and all cleft incidence (p>0.05), but a significant result was found between inadequate supplementation (<400µ/day) and cleft lip with or without cleft palate occurrence (p=0.043; OR 2.4[1.022-5.625]). Conclusion: The present study showed that most pregnant women did not have sufficient folic acid supplement in the first trimester. Furthermore, inadequate maternal folic acid supplementation (<400µ/day) during the first trimester of pregnancy increased the tendency for cleft lip and cleft palate (with or without cleft lip) to occur significantly.